Biosynthesis, Purification and Biotechnological Use of Exopolysaccharides Produced by Lactic Acid Bacteria - Werning, María Laura; Notararigo, Sara; Nácher, Montserrat; Palencia, Pilar Fernández de; Aznar, Rosa; López, Paloma (IntechOpen, 2012)
None